PENGARUH SELF EFFICACY DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BUSSON AUTO FINANCE (BAF) CABANG SURABAYA I - andjarwati, tri; setiawan, akhir putra (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACT PT. Bussan Auto Finance (BAF) Surabaya branch i. as a company that provides financing for credit to the General field of concentration on a Yamaha motorcycle financing. The presence of human resources at the company very important focused on self efficacy, motivation and performance of employees.Â The purpose of this research was to analyze the influence of self efficacy and motivation on performance of employees. The population used as respondents as many as 50 employees of the billing section. Data analysis using the Partial Least Square with the help of computer software to process data from a primary data collection. The results showed that there is a positive and significant influence self efficacy on performance of employees, there are also positive and significant influence motivation on performance of employees. Â Keyword:selfefficacy,motivation,employee performance